Analisis Akad Murabahah Dalam Pembiayaan Perumahan Melalui Pihak Ketiga - Azzahroh Nabila Al Wildany; Azzakiyatun Nisfu Laila Ramadhani; Farhan Wahyu Nurlian Panai; Sri Wigati (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study analyzes the implementation of the murabahah contract in housing financing conducted through third parties, particularly in situations where Islamic financial institutions do not fully acquire ownership of the property before reselling it to customers. Such a practice raises the possibility of non-compliance with the fundamental principles of murabahah, which require the bank to possess and bear risk over the asset prior to the sale. The research aims to evaluate customers’ level of understanding, their experiences during the financing process, and their perceptions regarding the sharia compliance of such practices. The research method employed an online survey by distributing a digital questionnaire via Google Forms to Islamic bank customers who have previously used or are currently using murabahah-based housing financing through third-party intermediaries. The collected data were analyzed descriptively to map patterns of perception and challenges faced by customers. The findings reveal that most respondents perceive the financing process as not fully reflecting the ideal murabahah mechanism, particularly concerning bank ownership of the asset and transaction transparency. These results indicate the need for stronger sharia compliance, especially in the areas of asset ownership and risk management by the bank. The study concludes that implementing murabahah through third parties requires strengthened regulation and enhanced customer education to ensure consistency with sharia principles. .